Analisis Faktor-Faktor Yang Mempengaruhi Produksi Padi Desa Pungka Kecamatan Unter Iwes Kabupaten Sumbawa - Iskamsiah Iskamsiah; Edi Irawan (Global Leadership Organizational Research in Management, 2024)
This research aims to determine whether or not there is an influence of each independent variable on the dependent variable. The independent variables used in this research are land (X1), capital (X2) and labor (X3). Meanwhile, the dependent variable in this research is rice production in Pungka Village, Unter Iwes District, Sumbawa Regency. This research uses multiple linear regression analysis techniques with the SPSS 23 application analysis tool. The data sources used are primary and secondary data obtained from related agencies and questionnaires to farmers in Pungka Village.